Social Stratification and Coping-Resilience Strategies as Mechanisms of Stunting in Urban Areas - Wahyuningsih, Endah; Kholifah, Siti; Chawa, Anif Fatwa; Utaminingsih, Alifiulahtin (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2025)
Urban stunting is not just a manifestation of malnutrition, but a complex phenomenon formed by social stratification, food policy, stigma, and community coping and resilience strategies. This study is a systematic narrative review of 30 international and national articles relevant to the issues of stunting, urban vulnerability, food policy, and coping-resilience. The analysis is carried out through thematic synthesis to identify patterns and interconnections. As a result, positions in social structures (class, gender, maternal education, economic status, and ethnicity) were identified as the main determinants of a child's vulnerability to malnutrition. Dietary practices are strongly influenced by food policies such as nutrition labeling, sugar-sweetened beverage taxes, and advertising restrictions, but the impact on stunting still varies between social groups due to limited purchasing power and nutritional literacy. Social stigma exacerbates inequality by restricting poor families' access to formal services. Meanwhile, coping strategies and community resilience capacity show an important mediating role: adaptive coping (problem-solving, community solidarity, faith-based support) strengthens the resilience of urban poor families, while maladaptive coping (reduction of meal portions, substitution of low-nutritious cheap food, selling productive assets) actually deepens the cycle of vulnerability. In conclusion, urban stunting must be understood as a reflection of structural health injustices as well as the adaptive capacity of households and communities. This study proposes an integrated framework that links social stratification (class, gender, ethnicity), food policy, stigma, and coping-resilience, as a basis for interventions that are equitable, culturally sensitive, and oriented towards strengthening the resilience of urban communities.